KOMUNITAS LITERER BANDUNG DALAM PERGERAKAN LITERASI INFORMASI - Ninis Agustini Damayani (Indonesian Journal of Dialectics, 2011)
This research was aimed to find the construction of self involvement meaning and the motive in information literacy movement, it was also to explore the experience of information literating and communicating from individuals that were involved in Komunitas Literer Bandung. Apart from participation observation and literature studies, data was gained from series of deep interviews with 15 individuals involved in Komunitas Literer Bandung that were divided into three groups, which are initiators and owners, organizers, and the members of Tobucil N Klabs, Rumah Buku/Kineruku, Zoe Cafe and Library, Potluck Coffee Bar and Library, and Ultimus.   The result of the research indicated that individuals involved in Komunitas Literer Bandung have constructed several meanings of self involvement, where motivation and hope were the aspects that urge their involvement. Establishing, developing and taking advantage of homy information literating places; making spesific literation activities; and having unique information literation regulations were their way of information literating. Furthermore, they established and developed kinship communication and partnership communication, through interpersonal communication, small-group communication, and online commmunication. This research also found that individuals involved in Komunitas Literer Bandung not only absorbed knowledge, but also expressed themselves, by becoming a part of the community, to build and construct knowledge  as a process of becoming a literate society; smart, critical and etical independent life-long learners.